Interconnections of Oral Microbiota and Systemic Health: Insights from Recent Research on Periodontal Diseases - Abirami Gunasekaran; Swetha Sunkar (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2025)
This review explores the intricate relationships between oral microbiota, periodontal diseases, and systemic health. Recent studies have revealed that alterations in the oral microbiome can significantly impact systemic conditions such as cardiovascular disease, diabetes, and rheumatoid arthritis. Pathogens such as Porphyromonas gingivalis and Tannerella forsythia are frequently implicated in these associations, contributing to systemic inflammation and disease progression. The review also examines how behavioral factors, particularly smoking and dietary habits, influence the composition of the oral microbiome and exacerbate periodontal conditions. Technological advancements in diagnostic methods, including multiplex real-time PCR and next-generation sequencing, have enhanced our understanding of microbial dysbiosis and its implications for disease severity. Furthermore, innovative therapeutic strategies such as Oral Microbial Transplantation (OMT) are being investigated to improve oral health outcomes. By elucidating these complex interactions, this review aims to inform healthcare professionals on effective strategies for the prevention and management of both periodontal diseases and their systemic implications.